Pendampingan Literasi Keuangan Era Digital Pada Generasi Millenial - Aslamiyah, Suaibatul; Reviandani, Wasti (JURNAL PENGABDIAN MANAJEMEN, 2024)
Technology that continues to develop nowadays makes it easier for the millennial generation to access various digital-based financial products and services. Financial technology (Fintech) has become an inseparable thing nowadays, but this convenience is often misused by irresponsible parties. So, financial literacy is very important for society, especially for the millennial generation. Especially the millennial generation is a social community that is literate and adaptable to technology. They tend to like using technology to make all activities easier, including shopping activities. The method used to carry out community service is Service Learning. The results of the service activities were that through the pre-test and post-test, it was found that the millennial generation's knowledge of Muhammadiyah 8 Gresik High School students increased in managing and planning finances. The 50/30/20 concept provides a way to plan and manage finances by distinguishing between needs, desires and savings which can be easily applied in relation to the problem of pocket money given by parents of the millennial generation.